SOSIALISASI TANGKAL RADIKALISME DI KALANGAN ANAK - ANAK KOMUNITAS MAT PECI CILIWUNG JAKARTA - Sandy Allifiansyah; Mitra Mustaricha; Qoryna Noer Seyma El Farabi; Salma, Muthia; Muhammad Vahlevi Rizal; Zacky Sazari Putra (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2025)
This community service focuses on efforts to prevent radicalism among children of the Mat Peci Ciliwung Community in Jakarta. The goal is to provide an understanding of national values, tolerance, and diversity from an early age. The methods used include socialization, training, discussion, and a child-friendly educational approach. Activities are carried out interactively through the delivery of visual materials and question and answer sessions. The results of the community service show an increase in children's understanding of the dangers of radicalism and the emergence of enthusiasm in expressing opinions and participating in discussions. This socialization is effective in forming children's characters who are critical, tolerant, and have a strong sense of nationalism.